Quantifying the effects of load carriage and fatigue under load on sacral kinematics during countermovement vertical jump with IMU-based method - McGinnis, R. S.; Cain, S. M.; Davidson, S. P.; Vitali, R. V.; Perkins, N. C.; McLean, S. G. (Sports Engineering, 2016)
We present a method for quantifying sacral kinematics during countermovement jumping (CMJ) using an inertial measurement unit (IMU). The IMU-derived sacral kinematic trajectories reproduced motion capture acceleration, velocity, and displacement to within mean (standard deviation) differences of 0.024 (0.088) m/s2, 0.023 (0.026) m/s, and 0.003 (0.032) m, respectively, across 252 jumps performed by 14 subjects. The method also quantified differences in maximum sacral displacement to within 1 % and differences in maximum propulsive velocity to within 0.7 % of motion capture estimates. This builds upon existing IMU-based methods for quantifying jump performance, which do not provide sacral kinematic trajectories. The utility of this method is demonstrated by its ability to discriminate jump performance metrics across a diverse subject population. In particular, we found that 21 participants adopted multiple strategies to maximize jump height in unloaded and loaded fresh conditions, but converged to a common strategy when jumping fatigued and under load. Changes in kinematic parameters were evident across conditions, and several changes were significantly associated with changes in jump performance (i.e., height). These parameters include changes in the depth of the countermovement, duration of the propulsive phase and maximum propulsive velocity. Collectively, these results point toward the future use of this method in naturalistic environments and for multiple objectives including biomechanical performance assessment and tracking, fatigue assessment, and jump training.